Exploiting Administrative Data to Understand the Mental Health of Children Known to Social Services - McKenna, Sarah; Maguire, Aideen; O'Reilly, Dermot (International Journal of Population Data Science, 2019)
Background Research has consistently found a high prevalence of mental ill-health among children in out-of-home care. However, results have varied significantly by study location, type of care intervention, sample population and mental health measurement, and concerns have been raised about appropriate reference populations. In addition, little is known about children known to social services who remain with their birth families. Aim To examine mental ill-health amongst children known to social services based on care exposure including those who remain at home, those placed in foster care, kinship care or institutional care and the general population not known to social services. Methods Northern Ireland is unique in that has an integrated health and social care system and holds data centrally on all children known to social services. Social services data (1995-2015) will be linked to hospital discharge data (2010-2015), prescribed medication data (2010-2015), self-harm data (2010-2015) and death records (2010-2015) to investigate mental health outcomes in terms of psychiatric hospital admissions, psychotropic medication uptake, self-harm and suicide. Results Data cleaning has been completed and analysis is underway. Preliminary results will be available by December 2019. Descriptive statistics will provide a mental health profile of children in care compared not only to children in the general population but to those who are known to social services but remain in their own home. Regression models will determine which factors are most associated with poor mental health outcomes. Conclusion This project is the UK’s first population-wide data linkage study examining the mental health of children in the social care system, including looked-after children and those known to social services who remain in their own home. Project partners in the Department of Health recognise the potential of these findings to inform future policy relating to targeting interventions for children in receipt of social care services.